The Z-Plasty Technique on the Frenectomy Approach of the Aesthetic Gingival Recession In Frenulum Labial Mandibular Case - Nuzulul Ismi; Ira Komara (Dentistry Faculty, 2020)
The frenulum is an anatomical structure in the oral cavity. Its formed folds of mucosa membranes attach the lip and the cheek to the alveolar mucosa, the gingiva, and the underlying periosteum. Abberansia frenulum is one of the causes of aesthetic and functional problems such as gingival recession, which occurs either due to plaque control or muscle pull issues. One of the treatment options for the anomaly of the frenulum case is by performing a frenectomy procedure. This paper aimed to explain using the z-plasty technique in abberansia frenulum treatment with hypertrophy frenum associated with midline diastema and short vestibule. A 36-year-old female patient came to Periodontic Clinic in Oral dan Dental Hospital, Universitas Padjajaran, Bandung, Indonesia, with chief complaint pain in 41 teeth, and clinically the gingiva appears recession and short vestibule. This situation is alarming in terms of aesthetics and functionality. The treatment of frenectomy with the z-plasty technique is an indication for this case. The frenectomy with the z-plasty method has shown favorable results in aesthetics and functional appearance. The z-plasty technique helped in reducing soft tissue tension so that it can minimize scar formation